(untitled) (Research, Society and Development, 2021)
Introduction: Delirium is a fluctuating state of cognition and consciousness, which can lead to memory loss, irritability, impaired collaboration and a dysregulated sleep-wake cycle. The prevalence of delirium in Intensive Care Units (ICUs) is related to a long period of time under mechanics, presence of severe pain, hypotension and higher mortality. A hospitalized elderly population is affected in about 15% by this morbidity, ranging to approximately 42%, dependent on associated comorbidities. Therefore, it is essential to gather evidence on the prevention of delirium in elderly patients admitted to the ICU. Methodology: This is an integrative literature review carried out in the SciELO, Medline and LILACS databases, with MESH descriptors and selected from articles published from 2017 to 2021, in any language, that were at the heart of the proposed objective. Exclusion criteria were: being an opinion article, review article, meta-analysis, trial protocol, pre-print or case report. Articles whose abstract, title or methodology did not match what was proposed in this review were also excluded. Results and discussion: Of 71 articles bulletins bulletins, 14 retrieved after applying the exclusion criteria. 7 were randomizations and 7 observational studies. Drugs such as melatonin, simvastatin, xenon, rameltheone, dexmedetomidine and others were added in elderly women in ICU with different comorbidities as potential prophylactic medications for delirium. In addition, non-pharmacological measures, such as night noise reduction, were also eliminated. We highlight the limitations imposed by the integrative review methodology itself, which has its result on the results and research of this study. Conclusion: There are pharmacological and non-pharmacological forms that reduce the impact of delirium in elderly patients admitted to the ICU, and that the heterogeneity of studies that build evidence must be considered, in order to favor the construction of a meta-analysis that statistically assesses them.